The Effect of Foreign Ownership, Sales Growth and Transfer Pricing on Tax Avoidance - Didi Sujadi; Ita Darsita; Kenne Mahendra (MultiTech Publisher, 2024)
The purpose of this study is to investigate how tax avoidance is affected by foreign ownership, sales growth, and transfer pricing in non-cyclical consumer sector companies that are listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022. The associative quantitative research design is employed. Purposive sampling was utilized to choose 114 samples from 11 non-cyclical consumer sector businesses based on predetermined criteria. Annual reports and audited annual financial reports of businesses acquired via the Indonesia Stock Exchange's official website serve as the source of the secondary data. Using the eViews 9 application software, panel data regression analysis and descriptive statistics are the data analysis methods employed.